Physical Fitness and its Relationship to Depressive Traits in Older Adults Undertaking Physical Activity - Rodriguez-Hernandez, Mynor (2014)
The purpose of this study was to determine the relationship between physical fitness and levels of depression in older persons involved in physical activity programs in San Ramon, Alajuela. A total of 138 older adults aged 60 to 86 years (67.94 ± 5.26) were assessed on the physical fitness using the SFT and levels of depression were measured using the GDS. Results suggest that about 97.8% of persons tested were within normal parameters and excellent on their physical fitness. Additionally, 86.2% of the cohort was found in a normal stage of depression. In addition, geriatric depression was negatively correlated with physical fitness on variables such as lower body muscle strength and endurance, arm muscle strength endurance, physical agility and dynamic balance, and lower body flexibility (p<0.05).  It is concluded that higher levels of physical fitness are associated with lower depression status in older adults.